Resensi Buku:: Writing/Reading the Bible in Postcolonial Perspective - Salomo Sihombing (Sekolah Tinggi Teologi Bandung, 2024)
The book Writing/Reading the Bible in Postcolonial Perspective, hereinafter referred to as